Binder’s Syndrome – An Unusual Craniofacial Anomaly - Madiyal, Ananya; Babu, Subhas; Ajila, Vidya; Castelino, Renita Lorina; Rao, Kumuda; Madi, Medhini (Journal of Dentistry Indonesia, 2018)
Binder’s syndrome or maxillonasal dysostosis is a rare congenital condition that primarily affects the mid-face and sometimes the vertebrae. It was named after von Binder who described three cases of hypoplastic maxilla-nasal complex in 1962. It can either occur as a sporadic mutation or may be inherited in an autosomal recessive pattern with incomplete penetrance. Decrease in the naso-labial angle, flat forehead, dish-shaped face, absence of protrusion of nasal tip, absence of nasal flare with triangular or semilunar nostrils, palpable depression in the nasal floor and a class III tendency are characteristic of the syndrome. Vertebral anomalies are seen in some patients owing to the parallel development of the nasal complex and vertebrae in the third month of intrauterine life. Prenatal diagnosis may be done using ultrasonography at 21 weeks of pregnancy. A multi-disciplinary approach towards planning of treatment for individuals with Binder’s syndrome includes orthodontic treatment along with osteotomies and grafting to correct the nasal and mid-face defects.